Reconfigurable metasurface emitters. Issue 11 (11th May 2022) - Pahlavan, Pooyan; Neshat, Mohammad
Abstract: In this article, we propose a reconfigurable metasurface emitter (MSE) with beam shaping capability without using any phase shifter or a superstrate. MSEs consist of repeating radiative inclusions (unit cells) distributed on a surface. The type, shape, geometry, and the arrangement of the radiative inclusions provide great flexibility to design high efficiency reconfigurable radiative surfaces with almost any desired property. Here, we propose a new metasurface emitter with parasitic inclusions for enhanced bandwidth and increased beam rotation as a special case of beam shaping. The design procedure of such MSE is explained, and its performance as an emitting surface is investigated through full wave simulations and measurements. In addition, we propose a technique for beam steering by integration of tunable components such as varactors to each inclusion. Using tunable components can provide reconfigurability for the radiated beam of MSE. Abstract : In this manuscript, we propose a reconfigurable metasurface emitter with beam shaping capability without using any phase shifter or a superstrate. Moreover, we demonstrate that by adding parasitic inclusions to the main inclusion, it is possible to enhance the bandwidth and consequently to increase the beam steering angle as a special case of beam shaping. The measurement results of a fabricated prototype of the proposed MSE verify our design procedure. Moreover, in our proposed structure each inclusion is fed as a radiator that is different from the previously proposed concepts using metasurface as a superstrate or a reflect or transmit array.